THU0356 Benefits of a multidisciplinary treatment in women with fibromyalgia and obesity. (23rd January 2014) - Castro, S.; Fontova, R.; Poveda, M.J.; Castel, A.; Qanneta, R.; Montull, S.; Periñan, R.; Miralles, I.; Aragonés, N.; Salvat, I.; Cascόn, R.; Monterde, S.; et al.
Abstract : Background: Fibromyalgia (FM) is a musculoskeletal chronic pain condition with low response to pharmacological conventional treatment (CPhT). Multidisciplinary treatment (MT) has showed efficacy in improving FM symptoms. Nevertheless, MT has not been studied in patients with FM and obesity. Objectives: To compare the benefits of the CPhT versus the MT (with pharmacological, cognitive-behavioural, and physiotherapy treatments) in a sample of women with FM and obesity (Body Mass Index ≥30). Methods: 44 women with obesity and FM according to the American College of Rheumatology criteria. Mean age 49.9 years (S.D. 6.4). 21 patients attended CPhT and 23 MT. Patients were assessed before treatment, after treatment, and at 3-6-12 month follow-up. Outcomes were: pain intensity (Numeric Rating Scale), functionality (FIQ), psychological distress (HADS), quality of life (COOP-WONCA), and sleep problems (Medical Outcome Study: MOS). Results: The interaction group x time with mixed linear model analyses demonstrated that patients of the MT group improved more than patients of the CPhT group in pain intensity (p<.001), functionality (p<.0001), quality of life (p<.05), and sleep index problems (p<.001). Conclusions: MT consisting of pharmacological treatment, cognitive-behavioural psychological treatment and physiotherapy improves FM symptoms in women with FM and obesity. Improvements were maintained at follow-up. Supported by the Foundation Maratό Grant Number 070910 Disclosure of Interest: None Declared